2021
DOI: 10.1016/j.cell.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

TMEM41B Is a Pan-flavivirus Host Factor

Abstract: Flaviviruses pose a constant threat to human health. These RNA viruses are transmitted by the bite of infected mosquitoes and ticks and regularly cause outbreaks. To identify host factors required for flavivirus infection, we performed full-genome loss of function CRISPR-Cas9 screens. Based on these results, we focused our efforts on characterizing the roles that TMEM41B and VMP1 play in the virus replication cycle. Our mechanistic studies on TMEM41B revealed that all members of the Flaviviridae … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
173
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 89 publications
(78 reference statements)
8
173
0
Order By: Relevance
“…Recent studies using genome-wide CRISPR/cas9 knockout screens with SARS-CoV-2 infection have identified a plethora of host factors important for productive infection by SARS-CoV-2 (Daniloski et al, 2021; Hoffmann et al, 2021; Schneider et al, 2021; Wang et al, 2021; Wei et al, 2021). The list of necessary host factors required for SARS-CoV-2 propagation varied widely among the different screens, likely due to different cell types and infection conditions used for each screen.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies using genome-wide CRISPR/cas9 knockout screens with SARS-CoV-2 infection have identified a plethora of host factors important for productive infection by SARS-CoV-2 (Daniloski et al, 2021; Hoffmann et al, 2021; Schneider et al, 2021; Wang et al, 2021; Wei et al, 2021). The list of necessary host factors required for SARS-CoV-2 propagation varied widely among the different screens, likely due to different cell types and infection conditions used for each screen.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being implicated for multiple flaviviruses, until very recently, there had been little follow-up or characterization. In January 2021, another study using genome-wide screening approaches for ZIKV and yellow fever virus host factors also identified TMEM41B as an essential host factor; in fact, it appears that TMEM41B is broadly required for most, if not all, flaviviruses [ 31 ]. Mechanistic studies with flaviviruses have revealed that TMEM41B physically interacts with the viral proteins NS4A and/or NS4B and is strongly relocalized to viral replication complexes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…4d), suggesting a role of TMEM41B in a post-entry step. A recent study also suggested a post-entry role of TMEM41B in flavivirus replication complex formation 30 . Together, these data identify the autophagy protein TMEM41B as an indispensable host factor for HCoV-229E.…”
Section: Pi3k Type 3 Is a Druggable Common Anti-coronavirus Targetmentioning
confidence: 96%